La facoltà di apportare modifiche nelle circoscrizioni ecclesiastiche dei territori di missione - Incitti, Giacomo (Ius missionale, 2010)
The faculty to Modify Ecclesiastical Circumscriptions in Mission Territories. The article analyzes the special faculty granted to the Congregation for the Evangelization of People to modify ecclesiastical circumscriptions belonging to mission territories (i.e. to modify territorial borders, denomination and to transfer the title of the cathedral Church). Following an historical overview of the context in which the faculty was granted, the juridical nature of the faculty is analyzed. The artical focuses on the procedure followed in the drafting phase of the request and the following decisional phase at Rome. The historical bachground and teh specific content of the faculty suggest to look on the opportunity of a greater devolution through the involvement of other ecclesiastical realities in the drafting phase of the request and in the decisional phase